Radiation Shielding for Medical Compact Cyclotron - HATAKEYAMA, Satoru; SERA, Kouichiro; HATANO, Kentaro; FUTATSUKAWA, Syoji; SAITO, Yoshihiro; SASAKI, Toshiaki (RADIOISOTOPES, 1993)
We are using a medical compact cyclotron for PET (positron emission tomography) and PIXE (particle induced X-ray emission) analysis in Nishina Memorial Cyclotron Center. The cyclotron vault is covered by concrete wall of 1.5 m thickness. However, a big penetrating window of 1.8 m square was needed at the concrete wall between the cyclotron vault and the PIXE room for beam transport equipment. This window was closed by packing materials of iron shots, small grained polyethylenes mixed with boron and lead grains for shielding of neutrons and γ-rays. Several measurement data have showed that this method is useful for shielding of radiations from the compact cyclotron.